The Relationship Between Social Media Addiction and Fear Of Missing Out - Lailil Mukarromah Ahmad; IGAA Noviekayati; Niken Titi Pratitis (AGUSPATI RESEARCH INSTITUTA, 2023)
The development of social media which is increasingly widespread and massive in all regions of the country and throughout the world community, including in Indonesia has penetrated various areas of life and can lead to higher social media addiction, which will also have an impact on the fear of missing out. Thus, this study aims to identify the relationship between social media addiction and the fear of missing out. The population in this study included men and women aged 18-40 years. With certain criteria set by the researcher. The sample in this study was 131 people. Validity test using an item discrimination test, and reliability test using Cronbach alpha. This research is quantitative, the method used is linear regression with the help of the Statistical Program for Social Science (SPSS) version 20 for Windows. The results of the analysis of social media addiction have a significant relationship to fear of missing out.